Molecular Breeding Strategy and Challenges Towards Improvement of Downy Mildew Resistance in Cauliflower (Brassica oleracea var. botrytis L.) - Shaw, Ranjan K.; Shen, Yusen; Zhao, Zhenqing; Sheng, Xiaoguang; Wang, Jiansheng; Yu, Huifang; Gu, Honghui (Frontiers in Plant Science, 2021)
Cauliflower (Brassica oleracea var. botrytis L.) is one of the important, nutritious and healthy vegetable crops grown and consumed worldwide. But its production is constrained by several destructive fungal diseases and most importantly, downy mildew leading to severe yield and quality losses. For sustainable cauliflower production, developing resistant varieties/hybrids with durable resistance against broad-spectrum of pathogens is the best strategy for a long term and reliable solution. Identification of novel resistant resources, knowledge of the genetics of resistance, mapping and cloning of resistance QTLs and identification of candidate genes would facilitate molecular breeding for disease resistance in cauliflower. Advent of next generation sequencing technologies (NGS) and publishing of draft genome sequence of cauliflower has opened the flood gate for new possibilities to develop enormous amount of genomic resources leading to mapping and cloning of resistance QTLs. In cauliflower, several molecular breeding approaches such as QTL mapping, marker-assisted backcrossing, gene pyramiding have been carried out to develop new resistant cultivars. Marker-assisted selection (MAS) would be beneficial in improving the precision in the selection of improved cultivars against multiple pathogens. This comprehensive review emphasizes the fascinating recent advances made in the application of molecular breeding approach for resistance against an important pathogen; Downy Mildew (Hyaloperonospora parasitica) affecting cauliflower and Brassica oleracea crops and highlights the QTLs identified imparting resistance against this pathogen. We have also emphasized the critical research areas as future perspectives to bridge the gap between availability of genomic resources and its utility in identifying resistance genes/QTLs to breed downy mildew resistant cultivars. Additionally, we have also discussed the challenges and the way forward to realize the full potential of molecular breeding for downy mildew resistance by integrating marker technology with conventional breeding in the post-genomics era. All these informations will undoubtedly provide new insights to the researchers in formulating future breeding strategies in cauliflower to develop durable resistant cultivars against the major pathogens in general and downy mildew in particular.